1999
DOI: 10.1143/jjap.38.l971
|View full text |Cite
|
Sign up to set email alerts
|

Universal Theory of Si Oxidation Rate and Importance of Interfacial Si Emission

Abstract: The essential role that Si atoms emitted from the interface play in determining the silicon-oxidation rate is theoretically pointed out, and a universal theory for the oxide growth rate taking account of the interfacial Si-atom emission is developed. Our theory can explain the oxide growth rate for the whole range of the oxide thickness without any empirical modifications, while the rate for an oxide thickness of less than 10 nm in dry oxidation cannot be explained with the Deal-Grove theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
159
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(162 citation statements)
references
References 28 publications
3
159
0
Order By: Relevance
“…7 An empirical equation, i.e., the D-G term plus an exponential term, proposed by Massoud et al 12 can only reproduce the observed growth rates numerically, but does not provide a physical meaning. The interfacial Si emission model 21 is now believed to be the model that can reproduce the observed oxide growth rate quantitatively very well. FIG.…”
Section: Discussion Of the Two Decelerating Stages In Terms Of Sicmentioning
confidence: 96%
See 2 more Smart Citations
“…7 An empirical equation, i.e., the D-G term plus an exponential term, proposed by Massoud et al 12 can only reproduce the observed growth rates numerically, but does not provide a physical meaning. The interfacial Si emission model 21 is now believed to be the model that can reproduce the observed oxide growth rate quantitatively very well. FIG.…”
Section: Discussion Of the Two Decelerating Stages In Terms Of Sicmentioning
confidence: 96%
“…It has been considered that oxide growth occurs only or mainly at the Si-oxide (SiC-oxide) interface. However, according to the Si emission model 21 for Si oxidation and the Si and C emission model 13 for SiC oxidation, Si atoms (Si and C atoms) are emitted into the oxide layer, some of which encounter the oxidant inside the oxide to form SiO 2 . When the oxide is very thin, some of the emitted Si atoms can go through the oxide layer and reach the oxide surface, and are instantly oxidized, resulting in the formation of an SiO 2 layer on the oxide surface.…”
Section: Discussion Of the Two Decelerating Stages In Terms Of Sicmentioning
confidence: 99%
See 1 more Smart Citation
“…8 A similar deviation in the thin oxide region has also been observed in Si oxidation, 9 and has been considered to result from a reduction in the reaction rate at the Si-SiO 2 interface due to the accumulation of Si atoms emitted into the SiO 2 layer. 10 Based on this idea, we proposed an SiC oxidation model, called the 'Si and C emission model', 11 in which it was assumed that Si and C atoms are emitted from the SiO 2 -SiC interface into the SiO 2 layer during oxidation and the interfacial oxidation rate is reduced if these atoms accumulate near the interface. To describe this initial deceleration process, we used an interfacial reaction rate that decreases as oxidation progresses, i.e., 11…”
mentioning
confidence: 99%
“…Since the thickness of sub-oxide is determined by the diffusion length of Si interstitial (independent of oxidation time), 10 the thickness should become constant at the steady-state. In addition, the growth of sub-oxide is transitioned to the steady-state at the very early oxidation stage because the emitted Si interstitials are instantly oxidized near the interface, as revealed in the Si oxidation.…”
mentioning
confidence: 99%